Bilaterally Combined Electric and Acoustic Hearing in Mandarin-Speaking Listeners: The Population With Poor Residual Hearing. (February 2018) - Tao, Duo-Duo; Liu, Ji-Sheng; Yang, Zhen-Dong; Wilson, Blake S.; Zhou, Ning
The hearing loss criterion for cochlear implant candidacy in mainland China is extremely stringent (bilateral severe to profound hearing loss), resulting in few patients with substantial residual hearing in the nonimplanted ear. The main objective of the current study was to examine the benefit of bimodal hearing in typical Mandarin-speaking implant users who have poorer residual hearing in the nonimplanted ear relative to those used in the English-speaking studies. Seventeen Mandarin-speaking bimodal users with pure-tone averages of ∼80 dB HL participated in the study. Sentence recognition in quiet and in noise as well as tone and word recognition in quiet were measured in monaural and bilateral conditions. There was no significant bimodal effect for word and sentence recognition in quiet. Small bimodal effects were observed for sentence recognition in noise (6%) and tone recognition (4%). The magnitude of both effects was correlated with unaided thresholds at frequencies near voice fundamental frequencies (F0s). A weak correlation between the bimodal effect for word recognition and unaided thresholds at frequencies higher than F0s was identified. These results were consistent with previous findings that showed more robust bimodal benefits for speech recognition tasks that require higher spectral resolution than speech recognition in quiet. The significant but small F0-related bimodal benefit was also consistent with the limited acoustic hearing in the nonimplanted ear of the current subject sample, who are representative of the bimodal users in mainland China. These results advocate for a more relaxed implant candidacy criterion to be used in mainland China.